Factors Affecting Carp Production in Floating Net Cages (KJA) in Tabir Lintas Sub-District Merangin District - Evo Afrianto; Danang Kuncoro; Pitriani Pitriani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Carp farming in Indonesia, especially in the Merangin Regency, has excellent potential to improve food security and farmers' welfare. This study analyzes the factors affecting carp production in floating net cages (KJA) in Tambang Baru Village, Tabir Lintas District. The research was conducted from March to April 2020, and 15 fish farmers were interviewed using the census method. The research variables included cage area, seeds, feed, and labor, with carp production as the dependent variable. Primary data were collected through interviews using a questionnaire, while secondary data were obtained from the Fisheries Service and the Central Statistics Agency (BPS). Data analysis used multiple linear regression with the help of SPSS to identify the influence of each variable. The results showed that seedlings significantly affected carp production, with a calculated T value of 103.291, higher than T table 1.81246. Meanwhile, cage size, feed, and labor did not show a significant effect on production. The R-square value reached 1,000, signifying a perfect correlation between the independent and dependent variables. This finding indicates that improving the quality of fingerlings can directly increase production, while other factors such as cage area, feed, and labor require further attention to improve the efficiency of carp production.